2021
DOI: 10.3390/machines10010004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nozzle Outlet Shape on Cavitation Behavior of Submerged High-Pressure Jet

Abstract: A submerged high-pressure water jet is usually accompanied by severe cavitation phenomenon. An organ pipe nozzle can greatly improve the cavitation performance of the jet, making use of the self-excited oscillation of the flow. In order to study the effect of organ pipe nozzles of different nozzle outlet shapes on cavitation behavior of submerged high-pressure jet, in this paper we build a high-pressure cavitation jet experiment system and carried out a high-speed photography experiment to study cavitation clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Dong [16] designed a diagonal nozzle with the k-ε model and researched the impact of intake constriction, parallel mid-section. Wang [17] used the proper orthogonal decomposition method (POD) to analyze cavitation cloud characteristics in organ pipe nozzles. Stanley et al [18] used direct numerical simulation (DNS) to study the creation of a free jet flow and the non-constant flow properties of a free-jet-flow shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Dong [16] designed a diagonal nozzle with the k-ε model and researched the impact of intake constriction, parallel mid-section. Wang [17] used the proper orthogonal decomposition method (POD) to analyze cavitation cloud characteristics in organ pipe nozzles. Stanley et al [18] used direct numerical simulation (DNS) to study the creation of a free jet flow and the non-constant flow properties of a free-jet-flow shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Topological optimization, aimed at minimizing mass [49][50][51][52][53][54] and developing cutting-edge micro-grippers [55], is also a crucial stage in the optimization process. To enhance interaction with the manipulated object, optimization of the active surface of the bodies in contact with the object [56][57][58][59][60] or the nozzle elements [61][62][63][64] responsible for forming the interacting flow are often employed.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the simulation results used under the RANS model differed from the actual flow field, and the numerical simulation results achieved via the RANS-LES and LES models agreed with the test results. The cavitating flow of the organ pipe nozzle was simulated by Wang et al [19] adopting the unsteady DES model. Akira et al [20] studied the vortex flow generated by the diesel nozzle with the LES method, and found that the LES could simulate the vortex structures better by comparing the results of this with the measured results.…”
Section: Introductionmentioning
confidence: 99%